Central corneal thickness and intraocular pressure in the Cameroonian nonglaucomatous population - André Omgbwa Eballe (Dove Medical Press, 2010)
André Omgbwa Eballe1, Godefroy Koki2, Augustin Ellong2, Didier Owono2, Emilienne Epée2, Lucienne Assumpta Bella2, Côme Ebana Mvogo1, Jeanne Mayouego Kouam21Faculty of Medicine and Pharmaceuticals Sciences, University of Douala; 2Faculty of Medicine and Biomedical Sciences, University of Yaoundé, CameroonAim: We performed a prospective, analytical study from 01 January to 31 March 2009 in the Ophthalmology Unit of the Gyneco-Obstetric and Pediatric Hospital of Yaounde, aiming to determine the profile of central corneal thickness (CCT) in the Cameroonian nonglaucomatous black population and its relationship with intraocular pressure (IOP).Results and discussion: Four hundred and eighty-five patients (970 eyes) meeting our inclusion criteria were selected for this study. The average CCT was 529.29 ± 35.9 µm in the right eye (95% confidence interval [CI]: 526.09–532.49), 528.19 ± 35.9 µm in the left eye (95% CI: 524.99–531.40) and 528.74 ± 35.89 µm in both eyes (95% CI: 526.48–531.00), range 440 to 670 µm. The average IOP was 13.01 ± 2.97 mmHg in both eyes (95% CI: 12.82–13.19). A rise in CCT by 100 µm was followed by an increase in IOP of about 2.8 mmHg (95% CI: 2.3–3.6) for both eyes taken together. Linear regression analysis showed that corneal thickness was negatively correlated with age and IOP was positively related with age.Conclusion: CCT in the Cameroonian nonglaucomatous black population was found to be lower compared with CCT values in Caucasian and Asian populations. On the basis of reference values ranging between 527 and 560 µm, an adjustment of IOP values by a correction factor is required for many Cameroonian patients. This will improve the diagnosis and follow-up of glaucoma by helping to detect true ocular hypertension.Keywords: central corneal thickness, intraocular pressure, Cameroon